SYNTHESIS OF NANOFIBER MEMBRANE FROM HIPS WASTE WITH ELECTROSPINNING METHOD AS AIR FILTRATION MEDIA - ZULFI M (NIM : 20215041), AKMAL
The synthesis of fibers from the waste of high impact polystyrene (HIPS) has been successfully done using electrospinning method. The HIPS solutions were made with a single solvent (DMF or d-limonene), mixed solvent (d-limonene/DMF) and also with the addition of acetone to the previously stated solvents. The effect of HIPS concentration, mix of solvent, and addition of acetone to the morphology and the diameter of fibers was observed. The morphological change from particles to fibers took place along with the increasing concentration of HIPS in d-limonene. For other precursor solutions using DMF as the solvent, bead free fibers could be obtained even at low concentrations. The average diameter of fibers increased along with the increasing concentration of HIPS in DMF. At the concentrations of 15, 20, 25, 30, and 35% of the average diameter obtained were 1.85 μm, 2.09 μm, 2.66 μm, 3.59 μm and 7.38 μm, respectively. For the precursor the which used the combination of solvents (d-limonene/DMF), the existence of beads was influenced by the ratio of solvents. When the ratio of HIPS / DMF was 100: 0, beaded fibers with are relatively large amount of beads were Obtained. At the ratio of 75:25, fewer beads were found. When the amount of DMF was Increased so the ratio of HIPS / DMF Became 50:50, even fewer beads Appeared. Bead-free fibers was finally Achieved Reached when the ratio 25:75. The addition of acetone reduced the diameter of fibers produced. However, too much addition of acetone would cause the fibers to be wet and the larger diameter Became after the addition of acetone well passed through Certain amount of volume. The synthesis of nanofibers membrane was conducted by first dissolving HIPS waste in a mixture of solvents of d-limonene and DMF(25/75, 50/50 and 75/25) to make the precursor solution. It was then electrospun into fibers by varying the duration into four variations (1, 1.5, 2, 2.5 and 4 hours) for a mix solvent d-limonene/DMF of 25/75, so there were resulted in nanofibers membrane with different thicknesses. For the test of air filtration process, we used aerosol which was consisted of PSL particles with a range of size(160, 216, 296, 451, 565 and 941 nm). It was then found that the highest efficiency was obtained from the nanofibers membranes synthesized at a duration of 4 hours with an average efficiency of 99.99% for each particle size. The lowest pressure drop was obtained from nanofibers membrane synthesized with a ratio of solvent d-limonene and DMF of 25/75. The thickness of the nanofibers membrane greatly affected the value of the pressure drop and the efficiency of the membrane.